A Treasury of stories for seven year olds - Blishen, Edward 1920-; Blishen, Nancy; Ludlow, Patricia (Kingfisher Books, 1988)
A collection of traditional and modern tales by such authors as Rudyard Kipling, Arthur Ransome, and Charles Perrault.